POLITIK HUKUM PERADILAN PAJAK DALAM SISTEM PERADILAN DI INDONESIA - Zulfikar, Muhammad Nahyan; Adabi, Muhammad Ikhwan; Muharrir, Muharrir (Prodi Ilmu Hukum, Universitas Teuku Umar, 2024)
AbstractThe problematic legal arrangement of the tax court as stipulated in Article 5 paragraph (1) and paragraph (2) of Law number 14 Year 2002 on Tax Court, paragraph (1)